Prospective study of self-reported diabetes and risk of upper gastrointestinal cancers - Lin, Shih-Wen (2011)
BACKGROUND: While gastric noncardia adenocarcinoma (GNCA) incidence rates in the US have decreased, the rates of gastric cardia adenocarcinoma (GCA) and esophageal adenocarcinoma (EADC) have increased. Obesity increases the risks of GCA and EADC, and the associations may be partially mediated by insulin resistance. A few case-control studies have shown an association between diabetes and an increased risk of EADC. METHODS: We prospectively examined the association between diabetes and upper gastrointestinal (UGI) cancers in a cohort of 469,448 people in the US, ages 50-71 at baseline. Cox proportional hazards regression was used to estimate the hazard ratios (HR) and 95% confidence intervals (CI) for diabetes and UGI cancers, controlling for multiple potential confounders, including body mass index (BMI). RESULTS: We observed no association of self-reported diabetes with risk of EADC, HR (95%CI) = 0.98 (0.73-1.31), esophageal squamous cell carcinoma (ESCC), HR (95%CI) = 1.02 (0.60-1.74), or GNCA, HR (95%CI) = 0.98 (0.70-1.37). However, diabetes was significantly associated with an increased risk of GCA, HR (95%CI) = 1.89 (1.43-2.50). The significant association between diabetes and risk of GCA remained after adjustment for BMI, HR (95%CI) = 1.70 (1.28-2.26) and did not differ by BMI strata (p(interaction) =0.83). The significant association was unchanged when restricting to only overweight subjects (BMI 25 - ≤30), HR (95%CI) = 1.83 (1.18-2.85). CONCLUSIONS: We found a significant association between self-reported diabetes and increased risk of GCA. IMPACT: Our results suggest that the metabolic and hormonal changes related to diabetes may play a role in the etiology of GCA independently from BMI.